2021
DOI: 10.1016/j.ultsonch.2021.105839
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound aided debittering of bitter variety of citrus fruit juice: Effect on chemical, volatile profile and antioxidative potential

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 60 publications
(85 reference statements)
1
11
0
Order By: Relevance
“…In reports of different effects on volatile compounds of thermal pasteurization and ultrasound treatment applied to pomegranate juice, ρ-cymene compounds decreased in both treatments, as in our study [ 67 ]. Similar effects were also detected after ultrasound was used to remove bitterness in citrus juice [ 14 ]. Ultrasound treatment preserved the total aldehyde amounts compared to thermal pasteurization.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…In reports of different effects on volatile compounds of thermal pasteurization and ultrasound treatment applied to pomegranate juice, ρ-cymene compounds decreased in both treatments, as in our study [ 67 ]. Similar effects were also detected after ultrasound was used to remove bitterness in citrus juice [ 14 ]. Ultrasound treatment preserved the total aldehyde amounts compared to thermal pasteurization.…”
Section: Resultsmentioning
confidence: 54%
“…Ultrasound technology is an alternative non-thermal technology to thermal processing that can be applied to many food products, fruit juices, and other products, such as vinegar, to increase the efficiency of unit processes generally applied in the food industry, ensuring food safety by helping to inactivate enzymes and microorganisms [ 4 , 8 , 9 , 10 , 11 ]. It was used for various foods, such as verjuice vinegar [ 5 ], tomato vinegar [ 4 ], Zhenjiangng vinegar [ 10 ], lactic acid fermented mulberry juice [ 12 ], red grape juice [ 13 ], mango juice [ 1 , 4 ], and citrus fruit juice [ 14 ] in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Naringin content decreased with an increase in the temperature from 40 to 60 • C at a constant treatment time. The lowest level of naringin content (5.35 mg/g) was observed at 60 • C. Previous studies reported that ultrasonication synergistically increased the catalytic activity of the naringinase enzyme that caused the hydrolysis of naringin and reduced the level of bitterness in grapefruit juice [33]. On a similar note, enhanced naringinase activity in Citrus maxima fruits at a temperature range of 45-65 • C was reported [34].…”
Section: Model Characteristics and Validationsupporting
confidence: 53%
“…Thermal pasteurization affected the 2‐heptanone compound 38.1% more than ultrasound treatment ( p > 0.05). At the end of the ultrasound applied to jujube vinegar, decreases in the octanal compound were similarly detected as the effect of ultrasound to removing bitterness in citrus fruit juice (Kumar Gupta et al, 2021). Tian et al, 2020 reported that ultrasound treatment preserved total alcohol volatile compounds more than thermal heat treatments, as in our study.…”
Section: Resultsmentioning
confidence: 94%
“…Ultrasound positively affects the number of antioxidants and phenolic compounds in products such as fruit, fruit juices, and vinegar (Golmohamadi et al, 2013). In literature studies, there was a minimum loss in bioactive components and nutritional properties of the products with ultrasound technology applications, such as pomelo juice (Gupta et al, 2020), citrus fruit juice (Kumar Gupta et al, 2021), purple onion vinegar (Yıkmış et al, 2022), ougan juice (Gao et al, 2021), and tomato juice (Starek et al, 2021). However, when the literature is examined, ultrasound studies are limited to increasing the quality of vinegar (Zhenjiang vinegar) (Wang et al, 2017), sherry vinegar (Jiménez-Sánchez et al, 2020), and verjuice vinegar (Yıkmış et al, 2020).…”
Section: Introductionmentioning
confidence: 99%